Frequency of Urinary Incontinence and Its Risk Factors in Patients Attending Gynae Outpatient Department (OPD) of Lady Reading Hospital (LRH) Peshawar, Pakistan: Urinary Risk Factors in Patients Attending Gynae Outpatient Department - Javed, Asiya; Bibi, Sadia; Firdus, Alia (Pakistan Journal of Health Sciences, 2025)
Urinary incontinence (UI) is an important health issue acknowledged by the World Health Organization (WHO) that adversely affects the quality of life. Objectives: To find out the occurrence of UI in female presenting to the Gynaecology Out-Patient Department of Lady Reading Hospital and also to find out the frequencies of its risk factors for urinary incontinence in women presenting with UI. Methods: A descriptive cross-sectional design was used to conduct this study. The sample consisted of 163 women who presented to the Gynaecology Out-Patient Department of Lady Reading Hospital for any complaints were included in the study. Results: UI was observed in 15.3% of patients. Moreover, Stress UI was 48%, followed by overflow UI 24%, urge UI 20%, and mixed UI 8%. The leading factors for UI consisted of 3.75% more than three normal vaginal deliveries, 24% chronic cough, 12% history of gynaecological operation, 80% Illiterate, and 56% lower urinary tract infection (LUTI). Conclusions: It was concluded that based on the findings of the current study, UI is 15.3% prevalent in Pakistan which is comparable to that of other Asian nations. Furthermore, normal vaginal delivery more than three times and UTI may develop the key risk issues for the development of UI. The magnitude of UI problems may impact on daily lives and habits of the patients.